The Use of Animated Film to Improve the Second Grade Students’ Writing Skill - Muhammad Dwiyan Aditiya (Universitas Ahmad Dahlan, 2018)
ABSTRACTThe article reveals (1) the description of the implementation of learning writing through the animated film; (2) the description of the second grade of science class students’ responses in learning writing through the animated film; and, (3) the improvement of the students’ writing skills in writing narrative text. The type of this research was classroom action research. The subject of this research was the second grade of science class students. The setting of this research was in one of public schools in Bantul, Yogyakarta. This research was carried out in two cycles which consist of four steps: planning, implementation, observation, and reflection. Each cycle consists of 3 meetings. Moreover, the data collecting technique of this research used qualitative and quantitative data. The qualitative data collecting techniques were observation checklists, interview guidance, and documentation; while, the quantitative data collecting technique was a writing test. Besides, the data analyzing technique of this research was the descriptive statistic and descriptive analysis. The descriptive statistic was used to analyse the quantitative data; while, the descriptive analysis was used to analyse the qualitative data. The results of this study revealed that the implementation of learning writing through the animated film was based on the lesson plan which consists of two cycles in which both the animated film and the writing practice was used and conducted. Moreover, the use of the animated film could also improve the students’ responses such as the students were not sleepy when teaching and learning through the animated film was conducted, the students paid attention to the animated film, the students answered the researcher’s question and the students could focus on writing. Furthermore, the use of the animated film could also improve the students’ mean score which was seen from preliminary research (66.5), post 1 (78.3), and post test 2 (83.0).Keywords: Writing, Senior High School Students, Animated film, Action research.